PERUBAHAN KONDISI SOSIAL EKONOMI MASYARAKAT SEBAGAI DAMPAK ADANYA PENGEMBANGAN OBJEK WISATA PANTAI OLELE - Kasim Mahmud; Yayu Indriati Arifin; Rusiyah Rusiyah (Universitas Negeri Gorontalo, 2021)
The research objective is to find out the Socioeconomic Of Community After The Development Of Olele Beach Tourist Attraction Olele Village Olele Villag Kabila Bone Sub-District Bone Bolango District. It applies a quantitative descriptive method while the data were collected through techniques of observasi, interview, and documentation. Research samples are determined by applying purposive sampling. Technique of processing data uses editing, sorting, tabulating, and interpreting. Meanwhile, technique of data analysis employes table of percentage and diagram. Findings of research show that the inpact of development of beach tourist attractionis positive on the change of livelihood or job, business opportunity, and community income. In addition, the developmentof Olele Beach Tourist Attraaction inpacts community positively as the open new businesses as employment opportunity around the spot such as food and drink stalls, other types of stalls, and bost whereas gazebo, snorkeling, and oksigen tank are othertypes new services that are for rent for the visitors or tourists. In total, 26 unit of new business have opened after the development, and they employ 34 people. Lastly, the change of socioeconomic after the devepolment of beach touist attraction in Olele Village is an increase of 26,4% in respondents' incomes who open a new business opportunity.